IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 34 TAHUN 2021 PASAL 30 TENTANG PENGGUNAAN TENAGA KERJA ASING DALAM KERANGKA TURNKEY PROJECT TIONGKOK DI PROVINSI RIAU - Fannisa, Meliana; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study analyzes how the implementation of Government Regulation Number 34 of 2021, Article 30, concerning the Use of Foreign Workers from China in Riau Province. There has been an increase in the number of foreign workers working in Indonesia, with foreign workers from China in the first place. Therefore, the Indonesian Government often tries to make changes to government regulations related to foreign workers to adjust to existing conditions. Government Regulation Number 34 of 2021, Article 30, is one of the results of changes to regulations regarding the obligation of foreign worker employers to provide Indonesian language training to foreign workers. This study uses a qualitative method, with data collection techniques through interviews and literature studies sourced from several books, journals, articles, and websites. This study uses the Neorealism perspective and Public Policy theory. The results of this study indicate that the implementation of Government Regulation Number 34 of 2021, Article 30, still requires further regulations so that guidance and supervision by related agencies can run. Keywords: Bahasa Indonesia, China, Foreign Workers, Government Regulation